Automatic Roof Control System in IoT-Based Clothes Drying Room: Sistem Pengendali Atap Secara Otomatis pada Ruang Penjemuran Pakaian Berbasis IoT - Yunus, Novia Setya Putri; Sulistiyowati, Indah (Indonesian Journal of Innovation Studies, 2021)
One of the problems that often occurs is that housewives are worried about their clothes getting wet in the rainy season. The automatic roof control system in the drying room is the best way to help the process of drying clothes in the rainy season. In this study, roof automation was developed using rain sensors and LDR as light detectors. NodeMCU esp3266 is also used so that the device can be controlled remotely with the Internet of Things system. The way this tool works is when the sun is hot the roof will open and when it rains the roof will close automatically, the heater and fan turn on simultaneously when the roof closes. The results of this study are the tool can detect rain and light then the heater and fan can work when the tool closes the roof with a maximum duration of 60 minutes. This tool can also operate remotely with the farthest range at 21 km.